Lower-extremity isokinetic strength profiling in professional Rugby League and Rugby Union - Brown, S. R.; Brughelli, M.; Griffiths, P. C.; Cronin, J. B. (International Journal of Sports Physiology and Performance, 2014)
Purpose: While several studies have documented isokinetic knee strength in junior and senior rugby league players, investigations of isokinetic knee and hip strength in professional rugby union players are limited. The purpose of this study was to provide lower-extremity strength profiles and compare isokinetic knee and hip strength of professional rugby league and rugby union players. Participants: 32 professional rugby league and 25 professional rugby union players. Methods: Cross-sectional analysis. Isokinetic dynamometry was used to evaluate peak torque and strength ratios of the dominant and nondominant legs during seated knee-extension/ flexion and supine hip-extension/flexion actions at 60°/s. Results: Forwards from both codes were taller and heavier and had a higher body-mass index than the backs of each code. Rugby union forwards produced significantly (P < .05) greater peak torque during knee flexion in the dominant and nondominant legs (ES = 1.81 and 2.02) compared with rugby league forwards. Rugby league backs produced significantly greater hip-extension peak torque in the dominant and nondominant legs (ES = 0.83 and 0.77) compared with rugby union backs. There were no significant differences in hamstring-to-quadriceps ratios between code, position, or leg. Rugby union forwards and backs produced significantly greater knee-flexion-to-hip-extension ratios in the dominant and nondominant legs (ES = 1.49-2.26) than rugby union players. Conclusions: It seems that the joint torque profiles of players from rugby league and union codes differ, which may be attributed to the different demands of each code.